Implementation of White Hat SEO-Based Digital Incubator Platform - Ihya Syihabul Fadli; Nuke Puji Lestari; Ananda Alifia Putri (International Transactions on Education Technology (ITEE), 2023)
Advances in information technology are developing rapidly in various areas of life. The Internet is one of the most influential information and communication technologies. A website, one of the Internet technologies, is not only a medium of information, but also a process that supports a company's business. No effect. SEO (Search Engine Optimization) is one of the advertising methods using search engine optimization so that the website created by our company will be displayed on the top of the search engine page or on the first page (first page). This research was initially conducted on the Business Incubator website, which did not follow his SEO techniques. Then some steps were also taken by implementing on-page SEO techniques such as title tag, content, meta keywords, keyword optimization for meta description and sharing on social media. This point. A test as a benchmark for successful implementation of SEO techniques. As a result of implementing SEO techniques, his website's SERP (Search Engine Results Pages) on search engines increased and in the second month he successfully landed on Google's second page and was indexed by Google Search. The first page was not successful in March.